Training For Patient Mobilization In Disaster Management: Safe And Efficient Transfer Techniques At The Sirajussa’adah Limo Islamic Boarding School, Depok - Suryani Maryam (Sean Institute, 2024)
In the wake of disasters, the efficient and safe mobilization of patients is a critical component of disaster management. This article explores the role of community service counseling in enhancing patient mobilization during such emergencies. Community service programs play a pivotal role in educating and training volunteers, healthcare professionals, and first responders on best practices for safely transferring patients to and from chairs, beds, long spine boards, and crutches. By focusing on the unique challenges presented by disaster scenarios, this counseling initiative aims to improve the preparedness of communities and healthcare systems. The program emphasizes the importance of proper techniques, coordination, and communication to minimize the risks associated with patient transfers in high-stress environments. Through case studies and practical examples, this article demonstrates how targeted counseling and training can significantly reduce injuries and improve outcomes during disaster response efforts. Ultimately, this work underscores the necessity of integrating community-based education into broader disaster management strategies to ensure that patient mobilization is handled with the utmost care and efficiency. The primary target of this community service activity is the students at Sirajussa'adah Limo Islamic Boarding School in Depok. The training methods, including lectures, discussions, simulations, and role-playing, are designed to teach patient mobilization techniques. The intended outcome is that students will be capable of providing immediate assistance with patient mobilization in the community, potentially reducing medical expenses for individuals and their families, thereby contributing to economic resilience.